IMPORTANCIA DE LA NUTRICIÓN INFANTIL PARA EL DESARROLLO DEL PAÍS. - KRONFLE RAMIREZ, JUAN ANDRÉS (2023)
Ecuador and Latin America over the years have suffered chronic child malnutrition, this is something that affects the growth of children who present complications in their growth stage and permanent damage in their adult life. The socioeconomic development of the countries that suffer from greater malnutrition is more affected with respect to countries that do not have such high rates, which is why governments take measures to curb this situation and reverse this problem to the extent possible. In this research we will analyze food projects that have been carried out, food that children need in the growth stage for adequate development, public policies that governments have taken in different countries of the region as a measure to combat malnutrition with their results. and correlations of the economies of the countries and the income with the rate of malnutrition suffered by their inhabitants.